Qualitative study of bereaved carers' experiences in advanced melanoma. (3rd June 2019) - Fox, J.A.; Langbecker, D.; Rosenberg, J.; Ekberg, S.
Summary: Melanoma is the deadliest form of skin cancer. In Australia, where this study was conducted, there were 1, 281 deaths from melanoma in 2016. Treatments for melanoma have changed rapidly in recent years with the introduction of immune and targeted therapies. These have resulted in longer term survival for some, but it is not clear which patients these treatments will work for, and for how long. This study aimed to understand the impact of melanoma treatments, as they relate to diagnosis and prognosis, on the experiences of family carers. Interviews were conducted with twenty carers of patients who were treated at three melanoma centres in Australia and who subsequently died. The study found that diagnosis of advanced melanoma was a time of uncertainty as carers struggled to understand the implications of the diagnosis. Treatment options in the form of relatively new immune and targeted therapies added to uncertainty around prognosis (i.e. the likely outcome, such as chance of survival). Carers reported unclear communication of prognosis by medical specialists. Some carers reported that medical specialists did not want or were not able to give a prognosis. Many carers expected that treatments would have positive outcomes. The study findings indicate that medical specialists should recognise and address carer understanding of and need for information about prognosis as early as possible following diagnosis. Communication of the uncertain benefit of these new therapies can help patients and carers make decisions about treatment preference and care planning. Abstract : Linked Article:  Fox et al. Br J Dermatol 2019; 180 :1368–1376